A network-based dashboard for cultural heritage promotion in digital environments. (2nd April 2019) - Capodieci, Antonio; Elia, Gianluca; Grippa, Francesca; Mainetti, Luca
This paper describes the design and application of a dashboard for visualising the interaction of content providers and online users with cultural objects within digital environments. The dashboard combines social network analysis metrics and content analysis indicators and relies on two-mode networks where nodes can be cultural heritage objects, institutional providers (galleries, museums) or individual digital content providers (experts and content aggregators). The links provide information about the digital resources associated to each object. The dashboard offers insights on the evolution of the most central providers, the most sought-after digital resources, and the most popular cultural objects over time. We applied the dashboard to an Italian living lab focused on cultural heritage and to a European platform for sharing cultural digital objects. Results show the emergence of clusters of interest around specific digital resources, and detect contributors sharing new topics of discussion and promoting innovative ways of organising the content.